Impact of globalization towards entrepreneurship career choice - Nor Hafiza Othman; Suraya Mahmood (2014)
Failure to see the opportunities that exist in the era of globalization have resulted in graduates is not alertness or sensitive to the entrepreneurship that can be used as an alternative career. This study aims to examine the university student's perception on impact of globalization on entrepreneurship career choice. Respondents in this study consist of 469 students from research university in Malaysia. The instrument used was questionnaire and data were analyzed using Statistics Package for Social Science (SPSS) for Windows Version 18. The findings indicate that most students understand the existence of globalization. The students's perception also scored moderately high on impact of globalization on entrepreneurship career. Further, the study found that significant relationship between impacts of globalization towards entrepreneurship career choice. Overall, this study indicates that the student understanding of globalization will affect their perception to choose entrepreneurship career. It is evident that student's knowledge on entrepreneurial opportunities that exist in the globalization will give advantage for them to become an entrepreneur. Therefore, the students should take initiative to involve entrepreneurship programmes to expose them in the challenging world of entreneurship to be more resilient and competitive entrepreneurs in global market.